ANALISA DELTA E PADA MATERIAL ASA INJECTION - Muhammad Yusuf Nurfani (Lembaga Pengembangan Kinerja Dosen, 2021)
Plastic Injection Molding (PIM) is a production process for the formation of plastic material from granular resin material used in making a manufacturing component. Defects that generally occur in plastic injection molding are short molds, which are conditions where the resulting part is not completely filled with plastic material. The research discusses the analysis of heat and E on the cover air flow against short mold defects. The method used is the actual calculation method and the actual analysis of the injection part and then compare the results of temperature variations. The material used in this research is ASA with grade LM5201F which is inserted into injection molding with a pressure of 96 Mpa. The temperature to be analyzed is 130̊C in the barrel. The results of this study show that a temperature of 150̊C with a cooling time of 21 seconds can overcome the problem of short mold on the cover air flow. For the results of E at a temperature of 130̊C, it has a higher value, namely 1.73, this is due to the cooling time which takes longer.